Capila jayadeva Moore, 1866 is a sexually dimorphic and male polymorphic species including six subspecies (Hesperiidae, Pyrginae) - Xue, Guo-Xi; Inayoshi, Yutaka; Saito, Kotaro; Li, Meng; Rao, Zhi (Zootaxa, 2026)
Despite the conspicuous different appearances in the males, Capila jayadeva Moore, 1866, C. translucida (Leech, 1893), C. hainana mackwoodi (Evans, 1914) and C. barroni (Riley & Godfrey, 1921) are proved to be conspecific based on an analysis of the 658 bp COI gene sequences, and the result is supported by the genitalia morphology. Considering the distinguishable wing patterns in the male and the allopatric distribution, the following subspecific combinations are proposed: C. jayadeva translucida, C. jayadeva mackwoodi, C. jayadeva barroni and C. jayadeva arooni Eliot, 1987. Therefore, with the nominate subspecies and C. jayadeva khambounei Uehara, 2024, the sexually dimorphic C. jayadeva currently includes six subspecies.